Comparison of TWINS and THEMIS observations of proton pitch angle distributions in the ring current during the 29 May 2010 geomagnetic storm. Issue 8 (8th August 2013) - Grimes, E. W.; Perez, J. D.; Goldstein, J.; McComas, D. J.; Valek, P.; Turner, D.
Abstract: [1] The first comparison between energy‐dependent ion pitch angle distributions in the ring current deconvolved from Two Wide‐angle Imagining Neutral‐atom Spectrometers (TWINS) energetic neutral atom (ENA) images and measured by Time History of Events and Macroscale Interactions during Substorms (THEMIS) D and E during a magnetic storm on 29 May 2010 is shown. The ion intensities and energy spectra along the THEMIS path are also compared with those deconvolved from the TWINS ENA images. The global plots of the ion intensities show an asymmetric ring current in the early recovery phase consistent with the ASY/H index. The comparison between the in situ pitch angle distributions observed by THEMIS and those obtained here from TWINS ENA images lends credence to the global plots of pitch angle anisotropy provided by the TWINS data. The spatial dependence of the pitch angle anisotropy provides information relevant to ion precipitation and lifetimes of trapped ring current ions not available from in situ measurements. Key Points: Global images of ion PADs obtained from TWINS ENA images are presented Global images of anisotropy are compared with in‐situ measurements by THEMIS Energy dependent PADs from ENA images are compared with measurements by THEMIS